CantasR A Green Technology for Oil Palm Harvesting and Customer Satisfaction towards Services Quality of CantasR Suppliers in Malaysia - Mat Sharif, Zainon; Jannah Jalil, Nurul; ., . (International Journal of Engineering and Technology, 2019)
Determining the relationship between customer satisfaction and services quality of CantasR suppliers was the major purpose of this study. The study employs empirical and descriptive design, with quantitative approach and purposive sampling using self-administrated questionnaires, were obtained from 30 smallholder respondents who is currently using CantasR from different supplier at the East Coast Region (Pahang state area), Peninsular Malaysia.  The study reveals that there was a convincing relationship between customer satisfaction and services quality of CantasR suppliers.  Therefore, it can be deduced that the service quality factors variable explains 73.20% of the variance that reflects the customer satisfaction on CantasR suppliers.  The overall finding shows that the service quality as tangibility, reliability, responsiveness, assurance and empathy did play a significant role in determining the customer satisfaction on CantasR suppliers.